Towards a systematic probabilistic evaluation of parentage casework in forensic genetics: a modest attempt to define a general standardized approach to simple and complex cases - Abrantes, D.; Pontes, M. L.; Pinheiro, M. F.; Andrade, M. A. P.; Ferreira, M. A. M. (Forensic Science International: Genetics Supplement Series, 2008)
In view of the increasing demand of ever-complex parentage casework, our lab saw itself in the position to define a strategy as standardized as possible to deal with the bulk of those cases. We searched for a coherent and exhaustive way to find answers. The major aim of this communication is to present the heuristical, mathematical and other aspects of a probabilistic evaluation procedure that has been developed since 2003. We also present a theoretical casework to illustrate one of the many problems that have to be faced: the choice of suitable statistical hypotheses.